Enhancing Vehicle Lifecycle Management through Integrated Data Platforms and IoT Connectivity (International Journal of Engineering and Computer Science, 2019)
The automotive business has transitioned from analogue to digital and is predicted to undergo an even bigger transformation, thanks to developments in digitalisation, artificial intelligence, and the Internet of Things (IoT). Comprehensive digital ecosystems will be developed by networks that comprehensively link vehicles, technology, services, and people with both external and internal environments. In these ecosystems, navigating the three-dimensional (3D) open space of vehicle, technology, service, and demand involvement will produce commercial values using digital twins and data and service platforms to signify investment return and technology selection across system capability, acceptability, and adaptability. By providing an integrated data platform and connection with IoT to bolster vehicle lifecycle management, a model with indicated objectives, landscapes, components, approaches, and supporting structures is proposed and illustrated. Additionally, the value empowerment of consumers leveraging the proposed model is discussed. An integrated data platform and connection with IoT must enable robust vehicle lifecycle management by deriving operational service use and condition parameters connected with owners, managers, and highways. The extensive interlinkages among vehicles, IoT components, and data and service components within the holistic digital ecosystem must be resolved for this purpose.The procedures to integrate all data and service components must be outlined, including crucial data management techniques for feature engineering, data cleansing, data enriching, and data refilling. Then, vehicle lifecycle management perspectives by data and service components are discussed, including insights into proactive in-market service design, dynamic from market service reconfiguration, robust operation support service design, and future out-of-market disruption identification. Central issues in vehicle lifecycle management, including design strategy, planning model and approach, service design strategy, and management approach, are considered following this. The overall landscape of the proposals and corresponding prospects is illustrated. Finally, industrial input and development is presented, notably the ultimate reference model for the holistic digital ecosystem, and threats, challenges, and future scope of research are discussed.